Safety and efficacy of fecal microbiota transplantation for autoimmune diseases and autoinflammatory diseases: A systematic review and meta-analysis - Zeng, Liuting; Deng, Ying; Yang, Kailin; Chen, Junpeng; He, Qi; Chen, Hua (Frontiers in Immunology, 2022)
Objective To evaluate the safety and efficacy of fecal microbiota transplantation for autoimmune diseases and autoinflammatory diseases. Methods Relevant literature was retrieved from the PubMed database, Embase database, Cochrane Library database, etc. The search period is from the establishment of the database to January 2022. The outcomes include clinical symptoms, improvement in biochemistry, improvement in intestinal microbiota, improvement in the immune system, and adverse events. Literature screening and data extraction were independently carried out by two researchers according to the inclusion and exclusion criteria, and RevMan 5.3 software was used for statistics and analysis. Results Overall, a total of 14 randomized controlled trials (RCTs) involving six types of autoimmune diseases were included. The results showed the following. 1) Type 1 diabetes mellitus (T1DM): compared with the autologous fecal microbiota transplantation (FMT) group (control group), the fasting plasma C peptide in the allogenic FMT group at 12 months was lower. 2) Systemic sclerosis: at week 4, compared with one of two placebo controls, three patients in the experimental group reported a major improvement in fecal incontinence. 3) Ulcerative colitis, pediatric ulcerative colitis, and Crohn’s disease: FMT may increase clinical remission, clinical response, and endoscopic remission for patients with ulcerative colitis and increase clinical remission for patients with Crohn’s disease. 4) Psoriatic arthritis: there was no difference in the ratio of ACR20 between the two groups. Conclusion Based on current evidence, the application of FMT in the treatment of autoimmune diseases is effective and relatively safe, and it is expected to be used as a method to induce remission of active autoimmune diseases. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021235055, identifier CRD42021235055.